The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/s2005-2901(09)60061-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Distilled Rehmannia glutinosa, Wild Ginseng and Astragali Radix Pharmacopuncture With Heart Rate Variability (HRV): A Randomized, Sham-controlled and Double-blind Clinical Trial

Abstract: This study compared the effects of distilled Rehmannia glutinosa, Wild Ginseng and Astragali Radix pharmacopuncture on the autonomic nervous system and heart rate variability. The purpose of the trial was to observe the influence distilled Astragali Radix, Wild Ginseng and Rehmannia glutinosa pharmacopuncture have on the autonomic nervous system. 120 healthy male volunteers were divided into four groups, which consisted of three experimental groups and a control group. This study was a randomized, placebo-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Another study suggested that P. ginseng suppresses apoptosis by regulation of Bcl-2 and caspase-3 during hypoxia/reoxygenation in neonatal rat cardiomyocytes [43]. The effects of wild ginseng and astragali radix pharmacopuncture have been compared on the autonomic nervous system and heart rate variability [44]. In addition, ginsenoside Rg 1 protects rat cardiomyocyte from hypoxia/reoxygenation oxidative injury via antioxidant and intracellular calcium homeostasis [45].…”
Section: Efficacy Of Improving Myocardial Protectionmentioning
confidence: 99%
“…Another study suggested that P. ginseng suppresses apoptosis by regulation of Bcl-2 and caspase-3 during hypoxia/reoxygenation in neonatal rat cardiomyocytes [43]. The effects of wild ginseng and astragali radix pharmacopuncture have been compared on the autonomic nervous system and heart rate variability [44]. In addition, ginsenoside Rg 1 protects rat cardiomyocyte from hypoxia/reoxygenation oxidative injury via antioxidant and intracellular calcium homeostasis [45].…”
Section: Efficacy Of Improving Myocardial Protectionmentioning
confidence: 99%
“…Wild ginseng pharmacopuncture in healthy adults tended to activate the autonomic nervous system, particularly the sympathetic nervous system [44]. Another clinical trial showed higher parasympathetic and lower sympathetic activity modulation after the administration of Kampo including ginseng [45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some of the meridian points have opposite effects, which are contrary to other points. LI11 [14] and GB21 [19] increase sympathetic nerve activity, while BL13 decreases it [20]. Since the point combinations in the holistic therapies include meridian points with bi-directional regulation of the autonomic balance, they can be applied to various pathological conditions in a balanced manner.…”
Section: Acupuncture and Moxibustion For Systemic Regulation Of The Amentioning
confidence: 99%